A Comprehensive Model for Executing Knowledge Management Audits in Organizations. Issue 1 (January 2015) - Shahmoradi, Leila; Ahmadi, Maryam; Sadoughi, Farahnaz; Piri, Zakieh; Gohari, Mahmood Reza
<x xml:space="preserve">Abstract</x> A knowledge management audit (KMA) is the first phase in knowledge management implementation. Incomplete or incomprehensive execution of the KMA has caused many knowledge management programs to fail. A study was undertaken to investigate how KMAs are performed systematically in organizations and present a comprehensive model for performing KMAs based on a systematic review. Studies were identified by searching electronic databases such as Emerald, LISA, and the Cochrane library and e-journals such as the Oxford Journal and hand searching of printed journals, theses, and books in the Tehran University of Medical Sciences digital library. The sources used in this study consisted of studies available through the digital library of the Tehran University of Medical Sciences that were published between 2000 and 2013, including both Persian- and English-language sources, as well as articles explaining the steps involved in performing a KMA. A comprehensive model for KMAs is presented in this study. To successfully execute a KMA, it is necessary to perform the appropriate preliminary activities in relation to the knowledge management infrastructure, determine the knowledge management situation, and analyze and use the available data on this situation.